Occult metastasis to the superficial level VI lymph nodes in papillary thyroid carcinoma. Issue 12 (21st September 2022) - Lee, Ha Na; Song, Chang Myeon; Ji, Yong Bae; Myung, Jae Kyung; Lee, Young‐Jun; Tae, Kyung
Abstract: Background: This study aimed to evaluate the incidence and risk factors of occult metastasis to superficial level VI, defined as the space anterior to the strap muscles, including the lymph nodes between the sternocleidomastoid and sternohyoid muscles and suprasternal space lymph nodes. Methods: We studied 129 patients with papillary thyroid carcinoma who underwent thyroidectomy and neck dissection, including superficial level VI dissection. Results: Of the 129 patients, 62 (48%) had lymph nodes in the harvested specimens of superficial level VI, and the mean number of lymph nodes retrieved was 1.9 ± 1.2. Occult metastasis to superficial level VI occurred in four patients (3.1%). No significant risk factors of superficial level VI occult metastasis were noted in multivariate analysis. Conclusions: Occult metastasis to superficial level VI was rare in patients with papillary thyroid carcinoma. Therefore, prophylactic dissection of superficial level VI may not be necessary for primary papillary thyroid carcinoma.